Transfer of Active Learning Strategies from the Teacher Education Classroom to PreK-12th Grade Classrooms - Susan Kaye Pepper; Sarah Blackwell; Ann Monroe; Shawn Coskey (Arizona State University, 2012)
In this study, researchers investigated the influence of modeling active learning strategies in an introductory foundations teacher preparation course: 1) on teacher candidates' perceptions of participating in active learning in the college classroom, 2) on participants' acquisition of course content, and 3) on participants' later use of active learning strategies in their classrooms as practicing teachers. Results revealed there was a significant difference in teacher candidates' acquisition of course content in the course sections that incorporated active learning (AL) and ones that incorporated a traditional lecture format (TL). In addition, on a follow-up survey of participants who are now practicing teachers, there was little difference in the use of the active learning strategies; however, there was a difference in the level of conceptual understanding of the theories of human development and diversity and how that knowledge was utilized by the AL and TL groups in their classrooms.